The people DataViz’s history ignores: a step forward to an intersectional history of Data Visualization - Esteves, Salomé (InfoDesign, 2023)
The history of Data Visualization, like history itself, has been told through the works of a narrow demographic group: white, cisgender men from high-income countries. While Florence Nightingale often features in such historical accounts and some recent literature has branched out to explore contributions from people with diverse gender and ethnical identities, a true feminist, intersectional, and decolonized History of Information Visualization is still missing. This paper attempts to jumpstart the effort of looking at women and people of color in Visualization’s past and examine the oppressive structures that hampered the deserved dissemination of their contributions.